2006
DOI: 10.1097/01.tp.0000230310.27913.01
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure Following Kidney Transplantation Associated with Myoglobinuria in Patients Treated with Rapamycin

Abstract: We conclude that myoglobinuria with myoglobin cast formation can occur following rapamycin administration, and may be a causative factor in the development of unexpected severe acute renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Acute tubular necrosis (ATN) is the histological diagnosis and principal cause of DGF. However, myoglobinuria and myoglobin casts have also been reported in four patients with sustained DGF (+14 days) among a series of 14 patients with myoglobin casts, and acute renal failure (ARF) was seen for 5–434 days post‐transplantation in eight of these patients, all of whom were receiving sirolimus [31].…”
Section: Delayed Graft Functionmentioning
confidence: 99%
“…Acute tubular necrosis (ATN) is the histological diagnosis and principal cause of DGF. However, myoglobinuria and myoglobin casts have also been reported in four patients with sustained DGF (+14 days) among a series of 14 patients with myoglobin casts, and acute renal failure (ARF) was seen for 5–434 days post‐transplantation in eight of these patients, all of whom were receiving sirolimus [31].…”
Section: Delayed Graft Functionmentioning
confidence: 99%
“…While in earlier reports it was a widely hold believe that the general cause of myoglobinuric ARF is the formation of myoglobin aggregates and renal tubular obstruction, leading to impairment of primary urine flow and reabsorption [8][9][10], recent studies have shown the development of oxidative stress under the conditions of myoglobinuria, accompanied by the increased production of ROS and lipid peroxidation [11,12]. The heme of a myoglobin molecule is thought to play the key role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study has shown low sensitivity to these indicators in an early renal damage [14]. Study also found a correlation of increased serum levels of Mb and early kidney damage caused by heart attack [15], suggesting that serum Mb, Scr, blood UN index all have the advantages of accuracy and high sensitivity in the diagnosis of early renal function damage in SHR [16]. Quite a large amount of evidence suggests that pathophysiological mechanisms involved in Mb uric conditions are associated with renal dysfunction as well as important laboratory morphologic considerations [17, 18] based on high serum Mb or tissue Mb.…”
Section: Introductionmentioning
confidence: 99%